Analysis Of The Impact Of Social Media On Student Learning Outcomes In Grade 5 Of SDN 7 Sambik Bangkol In The 2024/2025 Academic Year - Sahrul Sahrul; Ana Mulyono; Nunung Mardianti (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to describe the impact of social media on the learning outcomes of fifth-grade students at SDN 7 Sambik Bangkol in the 2024/2025 academic year. The research was conducted at SDN 7 Sambik Bangkol on fifth-grade students with a total of 41 students. This study focuses on the impact of social media on the academic performance of fifth-grade students. This is a qualitative study with a descriptive research design. The subjects of this study are fifth-grade students at SDN 7 Sambik Bangkol, focusing on the impact of social media on students' academic performance at school. The results of this study indicate that the impact of social media use on fifth-grade students at SDN 7 Sambik Bangkol is as follows: Social media affects students' focus on learning, social media affects students' motivation to learn, social media affects students' study time, the impact of social media on students depends on parental/teacher supervision, social media depends on the purpose of use (educational or entertainment), social media as a communication tool between students and teachers, social media addiction, and negative or age-inappropriate content (such as hoaxes, violence, etc.). From these impacts, we can conclude that students' study time is reduced due to excessive social media addiction, leading to a decline in academic performance among fifth-grade students at SDN 7 Sambik Bangkol.